Use of Critical Time Intervention (CTI) to Promote Continuity of Reintegration After Incarceration - Kim, Dae-Young (Criminal justice review, 2021)
Critical time intervention (CTI) is a time-limited intervention originally designed to provide the continuity of support for homeless and mentally ill people released from an institution to community living. This study offers theoretical foundations for adopting CTI in the field of criminal justice. Through the lens of CTI, this study examines the needs of prisoners returning to the community, discusses the challenges faced by reentry practitioners in offering support and assistance to ex-prisoners in the community, and provides specific suggestions. This study uses focus groups and individual interviews to assess the needs, obstacles, and opportunities ex-prisoners have or face in the community, as perceived by returning prisoners and practitioners, which leads to a more in-depth understanding of the prisoner reentry process.